THE ILLINOIS FULL VALUE ASSESSMENT LEGISLATION OF 1945 RELEVANT TO UNIFORMITY IN VALUATION OF REAL ESTATE UNDER THE GENERAL PROPERTY TAX* - Morrison, Vernon G. (Journal of Finance, 1962)
Abstract not available